Synergizing Omnichannel Order Management and CRM for Competitive Advantage: A Case Study of UNIQLO’s Digital Transformation - Andartya Setyawan Darna; Muharman Lubis (Yayasan Asmin Intelektual Berkah, 2025)
Intense competition in the retail industry requires companies to adopt an omnichannel strategy to create superior customer experience. This study aims to conduct an in-depth analysis of how UNIQLO, as a global retail leader, integrates Omnichannel Order Management (OOM) into its Customer Relationship Management (CRM) ecosystem. Adopting the omnichannel management framework, this study uses a qualitative case study approach based on secondary data to examine the strategies, technological enablers, and impacts of UNIQLO's